2022
DOI: 10.1101/2022.01.26.22269927
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Quick Displacement of the SARS-CoV-2 variant Delta with Omicron: Unprecedented Spike in COVID-19 Cases Associated with Fewer Admissions and Comparable Upper Respiratory Viral Loads

Abstract: Background The increase in SARS-CoV-2 infections in December 2021 in the United States was driven primarily by the Omicron variant which largely displaced the Delta over a three week span. Outcomes from infection with the Omicron remain uncertain. We evaluate whether clinical outcomes and viral loads differ between Delta and Omicron infections during the period when both variants were co-circulating. Methods Remnant clinical specimens from patients that tested positive for SARS-CoV-2 after standard of care … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 26 publications
3
59
0
Order By: Relevance
“…In addition, though RAT performance is in some studies less accurate in detection of the Omicron variant, the Flowflex™ has been shown to detect Omicron with reasonable sensitivity 23 . Similarly, while the decreased ability to culture Omicron has been reported 24 our culture assay system utilizing Caco2 cells overexpressing Ace2 and TMPRSS2 has good sensitivity for culturing SARS-CoV-2 variants including Omicron, 19,21 (JHC, unpublished data). Finally, and perhaps most significantly, both rapid antigen testing and culture are only proxies for transmission and correlates, not determinant, of infectiousness and transmissibility in vivo.…”
Section: Discussionsupporting
confidence: 60%
“…In addition, though RAT performance is in some studies less accurate in detection of the Omicron variant, the Flowflex™ has been shown to detect Omicron with reasonable sensitivity 23 . Similarly, while the decreased ability to culture Omicron has been reported 24 our culture assay system utilizing Caco2 cells overexpressing Ace2 and TMPRSS2 has good sensitivity for culturing SARS-CoV-2 variants including Omicron, 19,21 (JHC, unpublished data). Finally, and perhaps most significantly, both rapid antigen testing and culture are only proxies for transmission and correlates, not determinant, of infectiousness and transmissibility in vivo.…”
Section: Discussionsupporting
confidence: 60%
“…This increased shedding in part has been suggested to contribute to in the increased spread of these variants [19]. However, recent analysis of human specimens are indicative for no major differences in shedding between the SARS-CoV-2 variants Delta and Omicron BA.1 [20]. We demonstrated that the kinetics of viral genome shedding were not significantly different between Delta and Omicron BA.…”
Section: Previous Studies In Clinical Settings Have Shown That Viral ...mentioning
confidence: 54%
“…The copyright holder for this preprint this version posted March 15, 2022. ; https://doi.org/10.1101/2022.03.15.484448 doi: bioRxiv preprint recent analysis of human specimens are indicative for no major differences in shedding between the SARS-CoV-2 variants Delta and Omicron BA.1 [20]. We demonstrated that the kinetics of viral genome shedding were not significantly different between Delta and Omicron BA.1 infected hamsters.…”
Section: Discussionmentioning
confidence: 66%
“…Differences in viral levels between Omicron and Delta VOCs may also affect the detection of positive samples. RNA levels have been reported to be lower for the Omicron VOC when compared to Delta VOC [ 7 , 8 ], but higher in another more recent study [ 9 ], or similar in another one [ 10 ]. In the present study, the same Ct values were observed for Delta and Omicron VOCs, probably due to the type of sample analyzed (from travelers originally negative, retested 1–3 days later).…”
Section: Discussionmentioning
confidence: 74%